Anti-psychotic medication decision making during pregnancy: a co-produced research study. Issue 2 (2nd July 2019) - Pinfold, Vanessa; Dare, Ceri; Hamilton, Sarah; Kaur, Harminder; Lambley, Ruth; Nicholls, Vicky; Petersen, Irene; Szymczynska, Paulina; Walker, Charlotte; Stevenson, Fiona
Abstract : Purpose: The purpose of this paper is to understand how women with a diagnosis of schizophrenia or bipolar disorder approach medication decision making in pregnancy. Design/methodology/approach: The study was co-produced by university academics and charity-based researchers. Semi-structured interviews were conducted by three peer researchers who have used anti-psychotic medication and were of child bearing age. Participants were women with children under five, who had taken anti-psychotic medication in the 12 months before pregnancy. In total, 12 women were recruited through social media and snowball techniques. Data were analyzed following a three-stage process. Findings: The accounts highlighted decisional uncertainty, with medication decisions situated among multiple sources of influence from self and others. Women retained strong feelings of personal ownership for their decisions, whilst also seeking out clinical opinion and accepting they had constrained choices. Two styles of decision making emerged: shared and independent. Shared decision making involved open discussion, active permission seeking, negotiation and coercion. Independent women-led decision making was not always congruent with medical opinion, increasing pressure on women and impacting pregnancy experiences. A common sense self-regulation model explaining management of health threats resonated with women's accounts. Practical implications: Women should be helped to manage decisional conflict and the emotional impact of decision making including long term feelings of guilt. Women experienced interactions with clinicians as lacking opportunities for enhanced support except in specialist perinatal services. This is an area that should be considered in staff training, supervision, appraisal and organization review. Originality/value: This paper uses data collected in a co-produced research study including peer researchers.